2017
DOI: 10.1073/pnas.1705235114
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional regulation of Aβ levels by Presenilin 1

Abstract: Alzheimer's disease (AD) is characterized by accumulation of the β-amyloid peptide (Aβ), which is generated through sequential proteolysis of the amyloid precursor protein (APP), first by the action of β-secretase, generating the β-C-terminal fragment (βCTF), and then by the Presenilin 1 (PS1) enzyme in the γ-secretase complex, generating Aβ. γ-Secretase is an intramembranous protein complex composed of Aph1, Pen2, Nicastrin, and Presenilin 1. Although it has a central role in the pathogenesis of AD, knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…In the accompanying paper (22), we show that PS1 phosphorylation at Ser367 induces autophagic flux. To understand the molecular mechanism behind this effect, we examined neurons in the CA1 region of the hippocampus in PS1-S367A mice by transmission electron microscopy.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…In the accompanying paper (22), we show that PS1 phosphorylation at Ser367 induces autophagic flux. To understand the molecular mechanism behind this effect, we examined neurons in the CA1 region of the hippocampus in PS1-S367A mice by transmission electron microscopy.…”
Section: Resultsmentioning
confidence: 75%
“…3C). We have shown that CK1γ2 phosphorylates PS1 at Ser367 (22). Knock-down of Annexin A2 blocked the increase in Aβ40 induced by the compound 2-((4-(2-hydroxypropan-2-yl)phenyl)amino)-1H-benzo[d]imidazole-6-carbonitrile, a CK1γ inhibitor (Fig.…”
Section: Significancementioning
confidence: 79%
See 1 more Smart Citation
“…Zheng et al showed that Aβ production was suppressed 3-methyl adenine-dependent autophagy inhibition in vitro (Zheng et al, 2011). Aβ can be synthesized in the autophagosomes, which contain key mediators in its genesis (i.e., amyloid precursor protein and Presenilin-1) (Bustos et al, 2017). Also, tau post-translational modification can disrupt axoplasmic flow via autophagy, specifically through dynein-dynactin motors in vitro (Ikenaka et al, 2013).…”
Section: Autophagic-dependant Links Between Periodontal Disease and Smentioning
confidence: 99%
“…The discrepancy between these studies could be due to the fact that the use of mutations to mimic or abolish phosphorylation does not allow for assessing the dynamics of phosphorylation and the role of potential cross-talk between the phosphorylation at T3, S13 and S16. Furthermore, increasing evidence shows that the phosphomimicking mutations do not reproduce all aspects of protein phosphorylation (24,(39)(40)(41). We recently showed that the T3D mutation did not fully reproduce the inhibitory effect of T3 phosphorylation on the aggregation of Httex1 (24).…”
Section: Introductionmentioning
confidence: 96%